Physiological response of Moringa oleifera to stigmasterol and chelated zinc - ABDALLA EL-MOURSI; IMAN MAHMOUD TALAAT; MOHAMED ABDEL-GHANY BEKHETA; KARIMA GAMAL EL-DIN (Smujo International, 2012)
Abstract. El-Moursi A, Talaat IM, Bekheta MA, Gamal El-Din K. 2012. Physiological response of Moringa oleifera to stigmasterol and chelated zinc. Nusantara Bioscience 4: 118-123. Two pot experiments were carried out in the screen of the National Research Centre, Dokki, Giza, Egypt, during two successive seasons (2009/2010 and 2010/2011), respectively to study the effect of foliar spray with chelated zinc (100, 200 and 300 mg/L) and stigmasterol (50, 100 and 150 mg/L) on growth and chemical constituents of moringa plants (Moringa oleifera). The results indicated that treatment of plants with 300 mg/L chelated zinc or 150 mg/L stigmasterol significantly influenced the vegetative growth of moringa plants. The same treatments also significantly increased total sugars%, total protein%, total phosphorous and microelements contents in the leaves. The changes in the pattern of protein electrophoresis (SDS-PAGE) extracted from the newly formed leaves of moringa plants treated with different concentrations of chelated Zinc (Zn) or stigmasterol showed beneficial influences for improving plant growth, leaves quality and quantity.